2022
DOI: 10.3389/fphar.2022.895744
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Small-Molecule Inhibitor of SREBP-1 Based on Natural Product Monomers Upregulates the Sensitivity of Lung Squamous Cell Carcinoma Cells to Antitumor Drugs

Abstract: The transcription factor, sterol regulatory element binding protein 1 (SREBP-1), plays important roles in modulating the proliferation, metastasis, or resistance to antitumor agents by promoting cellular lipid metabolism and related cellular glucose-uptake/Warburg Effect. However, the underlying mechanism of SREBP-1 regulating the proliferation or drug-resistance in lung squamous cell carcinoma (LUSC) and the therapeutic strategies targeted to SREBP-1 in LUSC remain unclear. In this study, SREBP-1 was highly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 82 publications
1
9
0
Order By: Relevance
“…Mechanically, TPX2 mediates prostate cancer EMT through cyclin-dependent kinase (CDK1)-regulated phosphorylation of ERK/GSK3β/SNAIL pathway [ 73 ]. The results of this study show that TPX2 can function as a co-activator of PXR, which is consistent with some previous studies; Zhou et al found that TPX2 can act as a novel co-activator of ETS-1, and Sun et al found that TPX2 can promote endocrine dependence by facilitating the upregulation of AR activity and proliferation of prostate cancer cells [ 17 , 18 ]. It is worth mentioning that the nucleo-cytoplasmic migration of nuclear receptors and transcription factors represented by PXR is necessary for its normal physiological functions [ 74 , 75 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Mechanically, TPX2 mediates prostate cancer EMT through cyclin-dependent kinase (CDK1)-regulated phosphorylation of ERK/GSK3β/SNAIL pathway [ 73 ]. The results of this study show that TPX2 can function as a co-activator of PXR, which is consistent with some previous studies; Zhou et al found that TPX2 can act as a novel co-activator of ETS-1, and Sun et al found that TPX2 can promote endocrine dependence by facilitating the upregulation of AR activity and proliferation of prostate cancer cells [ 17 , 18 ]. It is worth mentioning that the nucleo-cytoplasmic migration of nuclear receptors and transcription factors represented by PXR is necessary for its normal physiological functions [ 74 , 75 ].…”
Section: Discussionsupporting
confidence: 93%
“…For cellular experiments, the four TKIs, the three cytotoxic chemotherapeutic drugs, irinotecan, paclitaxel, and etoposide, and the pure powders of these seven drugs were first weighed accurately using a precision balance (1/100,000 precision required) and then dissolved in the organic solvent dimethylsulfoxide (DMSO). In the process of dissolving these pure drug powders, stirring, vortexing, and ultrasonic vibration were used to assist dissolution [ 17 , 18 ]. After a drug was fully dissolved, Dulbecco’s modified Eagle’s medium (DMEM) without fetal bovine serum (FBS) was used to dilute the drug dissolved in DMSO.…”
Section: Methodsmentioning
confidence: 99%
“…The PI3K/AKT/mTOR signaling pathway is involved in a variety of pathological mechanisms, including proliferation, apoptosis, metastasis, invasion, and angiogenesis ( 40 , 48 ). Deregulation of the PI3K/Akt/mTOR pathway leading to activation is common in HCC and is hence the subject of intense investigation and the focus of current therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the malignancy develops rapidly in the middle to late stage, leading to the poor prognosis of patients with HCC. Moreover, for patients with cirrhosis, the risk of progression to HCC is high, so early diagnosis of HCC, especially in patients with cirrhosis, is particularly important (5)(6)(7)(8)(9). At present, alpha-fetoprotein (AFP), the most commonly used tumor marker in HCC, has a poor diagnostic performance (10,11).…”
Section: Introductionmentioning
confidence: 99%